The time delay between when patients present with symptoms of tuberculosis at TC Newman Hospital, Paarl and the start of their treatment - Chantal Fourie; Carli Hennig; Adre Lourens; Esther Basson; Andre Klop (South African Family Practice)
No abstract available.